A Comprehensive Review on Anti-Cancer Properties of Oxalis corniculata - Kumar, Arun; Maurya, Sharmila; Kant, Shiva; Kumar, Anuj (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Oxalis corniculata L. belongs to the Family (Oxalidaceae), commonly known as “creeping woodsorrel, procumbent yellow sorrel, or sleeping beauty, " a common name. Oxalis corniculate contains several compounds like β-sitosterol, betulin, 4-hydroxybenzoic acid, ethyl gallate, methoxyflavones, apigenin, and 7-O-β-D-glucopyranoside were previously isolated from the whole plant of Oxalis corniculata. linn. The review reveals that wide ranges of phytochemical constituents have been isolated from the plant like flavonoids, tannins, phytosterols, phenol, glycosides, fatty acids, galactose-glycerolipid, and volatile oil. The leaves contain flavonoids, iso vitexin, and vitexin-2”- O- beta – D- glucopyranose. It is a rich source of essential fatty acids like palmitic, oleic, linoleic, linolenic, and stearic acids. It has been reported that the plant contains anti-inflammatory, anxiolytic, anticonvulsant, antifungal, antiulcer, antinociceptive, anticancer, antidiabetic, hepatoprotective, hypolipidemic, abortifacient, antimicrobial, and wound healing properties.